Antagonistic potential of soil fungi against Colletotrichum gloeosporiodes (Penz.) Sacc., the causal agent of anthracnose of Rauwolfia serpentina (L.) Benth. ex Kurz - Yasmin, Zuhra; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2019)
Four antagonistic fungi Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tiegh. and Trichoderma viride Pers. were isolated from field soil of Rauwolfia serpentina by serial dilution method and selected to evaluate their antagonistic potentiality against Colletotrichum gloeosporiodes (Penz.) Sacc, the causal agent of anthracnose of Rauwolfia serpentina (L.) Benth. ex Kurz following dual culture colony interaction, volatile and non-volatile metabolites. In dual culture method Trichoderma viride showed maximum (84.28%) inhibition of test fungi followed by Aspergillus niger (77.39%), A. fumigatus (43.71%) and A. flavus (29.32%). Volatile metabolites of T. viride showed higher (77.64%) inhibition of test fungi followed by A. flavus (75.58%), A. fumigatus (60.88%) and A. niger (58.23%). Non-volatile metabolites of antagonistic fungi showed that A. flavus showed (94.42%) inhibition of test fungus followed by T. viride (90.90%), A. niger (86.13%) and A. fumigatus (73.73%). Aspergillus flavus, A. niger and T. viride may be exploited commercially as a biocontrol agent against anthracnose disease of R. serpentina. Dhaka Univ. J. Biol. Sci. 28(2): 219-226, 2019 (July)